2019
DOI: 10.1093/nutrit/nuz023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saffron supplementation on symptoms of depression and anxiety: a systematic review and meta-analysis

Abstract: Context Saffron (Crocus sativus L.) has gained interest as a potential treatment in psychiatry. Objective This systematic review and meta-analysis sought to investigate the effect of saffron supplementation, as both an adjunctive therapy and monotherapy, on symptoms of depression and anxiety in clinical and general populations compared with pharmacotherapy or placebo. Data sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 46 publications
3
50
0
6
Order By: Relevance
“…Additionally, repeated oral administration reduced anhedonic behavior, assessed in the sucrose preference test—an effect that was not observed under ip administration. Overall, these results are congruent with reports describing the beneficial effects of saffron extract consumption in patients suffering from anxiety or depression [ 41 , 42 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, repeated oral administration reduced anhedonic behavior, assessed in the sucrose preference test—an effect that was not observed under ip administration. Overall, these results are congruent with reports describing the beneficial effects of saffron extract consumption in patients suffering from anxiety or depression [ 41 , 42 ].…”
Section: Resultssupporting
confidence: 91%
“…Additionally, there is also growing evidence supporting the antidepressant and anxiolytic effects of saffron in humans suffering from depression and anxiety. Thus, saffron extracts can relieve the severity of symptoms of depression and the effect of saffron extracts resemble those of tricyclic (TCA), Selective Serotonin Reuptake Inhibitors (SSRI) and Selective Noradrenaline Reuptake Inhibitors antidepressants in depressed patients [ 41 , 42 ]. Saffron extracts, when administered in combination with pharmacological antidepressants, were also shown to improve some scores related to depression, even in subjects who had been using the antidepressants with no improvement [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…e fast presence of crocetin in blood plasma after the administration of the saffron extract contributes to better explain saffron beneficial effects in animal models [48]. e commercial standardised saffron extract affron ® used in this study is related to beneficial effects in depression and mood disorders by several clinical trials at the dosage used in the present work [13,14,16] and in the reduction of inflammatory damage in the retina in an animal model of glaucoma [20]. e obtained results in this study increase the interest of saffron extract use as a new preventive therapy that requires a fast-active countereffect, for instance, as "fast-track" carotenoid in the Aged-Related Eye Disease Study (AREDS-2) formula.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the clinical evidences of saffron extracts have been accumulated and has been postulated as a complementary therapy in several medical conditions. In particular, to delay the occurrence of the symptoms and effects of degenerative ocular diseases [8] and to prevent and treat mood disorders and mild-to-severe depression without side-effects, even in people with unremitted depression treated with antidepressant medication [12][13][14][15][16]. In depression, different mechanisms of actions have been proposed to explain the functional properties of saffron such as reuptake inhibitors of monoamines, N-methyl-Daspartate receptor (NMDA) antagonism, and gamma-aminobutyric acid (GABA) agonism [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to increasing positive findings associated with nutraceutical and herbal supplementation on depressive and anxiety symptoms, a PI Therapy plus supplements arm was included in this study to examine whether the addition of supplements to an integrative intervention could enhance treatment outcomes. In several meta-analyses, it has been confirmed that supplementation with saffron, 32 curcumin, 33 probiotics, 34 and omega-3 fatty acids 35 are associated with reduced depressive and/or anxiety symptoms. However, most studies have been stand-alone interventions and the efficacy of supplementation as a component of a comprehensive integrative intervention has received little attention in the scientific literature.…”
mentioning
confidence: 95%